A transcriptome analysis of mitten crab testes (Eriocheir sinensis) - Zhang, Wei (Sociedade Brasileira de Genética, 2011)
The identification of expressed genes involved in sexual precocity of the mitten crab (Eriocheir sinensis) is critical for a better understanding of its reproductive development. To this end, we constructed a cDNA library from the rapid developmental stage of testis of E. sinensis and sequenced 3,388 randomly picked clones. After processing, 2,990 high-quality expressed sequence tags (ESTs) were clustered into 2,415 unigenes including 307 contigs and 2,108 singlets, which were then compared to the NCBI non-redundant (nr) protein and nucleotide (nt) database for annotation with Blastx and Blastn, respectively. After further analysis, 922 unigenes were obtained with concrete annotations and 30 unigenes were found to have functions possibly related to the process of reproduction in male crabs – six transcripts relevant to spermatogenesis (especially Cyclin K and RecA homolog DMC1), two transcripts involved in nuclear protein transformation, two heat-shock protein genes, eleven transcription factor genes (a series of zinc-finger proteins), and nine cytoskeleton protein-related genes. Our results, besides providing valuable information related to crustacean reproduction, can also serve as a base for future studies of reproductive and developmental biology.